Multimedia and its applications - Zeki, Akram M. (IIUM Press, 2015)
Multimedia system could be defined as the combination of computer hardware and software designed so as to create, store and disseminate multimedia content. Multimedia techniques enable users to record, play, display or access information from different sources at the same time. This book provides the basis and fundamental procedures needed for the processing devices to implement multimedia techniques. Readers of his book would acquire in-depth knowledge of multimedia components and its applications as well as be exposed to the characteristics of multimedia files forma and the application of multimedia in different fields. Students and others interested in multimedia applications would find this book a useful asset.